2011
DOI: 10.1021/ac201318z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Weak Absorption Changes from Molecular Events in Time-Resolved FT-IR Spectromicroscopy Measurements of Single Functional Cells

Abstract: The possibility of performing FT-IR spectromicroscopy experiments on individual living cells is the focus of considerable attention. Among the applications of interest, the obtainment of structural information in rapid measurements, with a time resolution of the minute or better, is a prized goal. In this work, we show that the use of synchrotron FT-IR spectromicroscopy allows one to extract weak spectral changes, of less than 10(-3) au per minute, in the absorption spectrum of single rod cells following photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…35 The second derivative of the asymmetric stretching band of phosphate moieties, PhI hereafter, of MDA-MB 231 cells displays two major components centered at 1241 and 1218 cm −1 , conventionally assigned to the A and B helices of double stranded nucleic acids ( Figure S1c in the Supporting Information). 36,40 The symmetric stretching band of phosphates, PhII from here on, is centered at 1085 cm −1 and two shoulders related to stretching modes of ribose and polysaccharides are centered at 1120 and 1050 cm −1 , respectively. 37 MDA-MB 231 cells measured at a constant temperature of 37 ± 0.5°C for 2 h do not show significant spectral changes in both position and relative intensities of the second derivative peaks, as can be appreciated from Figure S2a in the Supporting Information.…”
Section: ■ Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…35 The second derivative of the asymmetric stretching band of phosphate moieties, PhI hereafter, of MDA-MB 231 cells displays two major components centered at 1241 and 1218 cm −1 , conventionally assigned to the A and B helices of double stranded nucleic acids ( Figure S1c in the Supporting Information). 36,40 The symmetric stretching band of phosphates, PhII from here on, is centered at 1085 cm −1 and two shoulders related to stretching modes of ribose and polysaccharides are centered at 1120 and 1050 cm −1 , respectively. 37 MDA-MB 231 cells measured at a constant temperature of 37 ± 0.5°C for 2 h do not show significant spectral changes in both position and relative intensities of the second derivative peaks, as can be appreciated from Figure S2a in the Supporting Information.…”
Section: ■ Resultsmentioning
confidence: 85%
“…The applicability of 2D correlation analysis for the investigation of a complex system, such as a live cell, has been reported by other authors. 39,40 It is however undoubtable that establishing the fine dynamic of protein folding by this technique is challenging even for pure proteins, and it is further complicated by the complexity of the cellular machinery. The task is even more challenging in our case, since, as it will be better clarified in the Discussion, the nature of the events related to HSR is regulated by a dynamic equilibrium that can be shifted to reagents (native proteins) or products (β-aggregates) depending on a multitude of factors, first of all the individual cellular susceptibility to the stress.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In applications to complex biological systems it has been shown that the analysis allows the identification of bands arising from the same molecular chromophore. 40,42 Additional features that make 2D-COS useful for the analysis of cellular spectral patterns are the improved spectral resolution and the possibility to extract weak bands evolving on a noisy background. 40,43 The results of a 2D-COS analysis of the spectral changes from figure 3 are shown in From uptake measurements, it is assumed that the observed concentration increase is localized within the cell or at its surface.…”
Section: D-cos Was Introduced By Noda As a Tool Tomentioning
confidence: 99%
“…The generalized 2DCOS can elucidate information in spectral variations, e.g., IR (Kim et al, 2006b; Cerdà-Costa et al, 2009; Huang et al, 2009; Unger et al, 2009, 2011; Del Río et al, 2010; Huang and Kuo, 2010; Jelèić et al, 2010; Jia et al, 2010; Lee et al, 2010, 2012; Peng et al, 2010; Popescu and Vasile, 2010, 2011; Zheng et al, 2010; Cheng et al, 2011; Jin et al, 2011; Kuo and Liu, 2011; Musto et al, 2011; Quaroni et al, 2011; Wang and Wu, 2011; Zhang et al, 2011; Ando et al, 2012; Qu et al, 2012; Su et al, 2012; Wu et al, 2012; Chai et al, 2013; Lai and Wu, 2013; Park et al, 2013; Shinzawa et al, 2013; Wang et al, 2013, 2014; Galizia et al, 2014; Hou et al, 2014; Noda, 2014c; Seo et al, 2014), Raman (Radice et al, 2010; Tang et al, 2010; Ma et al, 2011; Ji et al, 2012; Pazderka and Kopecký Jr, 2012; Brewster et al, 2013; Grzeszczuk et al, 2013; Noda, 2014d), terahertz (THz) (Hoshina et al, 2012, 2014), X-ray (Guo et al, 2011), UV-Vis (Hong et al, 2005; Jiang and Wu, 2008; Sikirzhytski et al, 2012; Zhong et al, 2012), NMR (Oh et al, 2009; Li et al, 2013), fluorescence (Hur et al, 2011; Zhang et al, 2013), and even chromatography (Izawa et al, 2001), under various external perturbations, such as thermal, electrical, optical, magnetic, and chemical perturbations (Noda, 1986, 1993; Hong et al, 2005; Kim et al, 2006b; Jiang and Wu, 2008; Cerdà-Costa et al, 2009; Huang et al, 2009; Oh et al, 2009; Unger et al, 2009; Del Río et al, 2010; Huang and Kuo, 2010; Jelèić et al, 2010; Jia et al, 2010; Lee et al, …”
Section: Introductionmentioning
confidence: 99%